Relationship Between Periodontal Inflamed Surface Area( PISA) and Serum Markers in Diabetic Patients Undergoing Hemodialysis - Swathi Vathsa 21D03104; Dr.Vidya Priyadharshini (JSS AHER, Mysuru JSSDC, Mysuru, 2021)
1. Introduction, 2.Aims &Objectives, 3.Literature Review,4.Methodology,5.Results,6.Discussion, 7.Conclusion,8.Summary, 9. References, 10.Annexures
Keywords: Periodontology